Pengurangan Kadar N dan P pada Limbah Cair Laboratorium secara Fitoremediasi Menggunakan Enceng Gondok (Eichornia crassipes) - Nurmaya Arofah; A. Silvan Erusani (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2014)
Laboratory liquid waste contains both metal, nonmetal, organic and anorganic content. If it is discharged directly to environment, it will cause pollution that is harmful for living thing. Data of waste survey result in 2009-2010 indicated that liquid waste of Laboratory in Chemical Engineering Department, Gadjah Mada University (JTK UGM) consist of various complex compound such as NH4+, PO43-. JTK UGM has wastewater treatment plant (WWTP) to deal with environmental pollution coming from waste of each laboratory and have three process, anaerobe activated sludge, aerobe and phytoremediation. Because the laboratory’s waste was very complex, the WWTP have not operated maximally yet. So, it is necessary research on wwtp processing step, particularly for phytoremediation process using water hyacinth. Objective of this research was to study effect of concentrations N and P on adaptability and capability of water hyacinth to grow. In addition it developed a mathematical model to estimate of N and P concentration decrease rate in liquid. The research was done in batch by planting water hyacinth that has been acclimated in wastewater containing N-NH4OH and P-H3PO4. Parameter observed is N and P concentration in liquid. The result indicated that water hyacinth can absorb N and P. Water hyacinth grow well in N-NH4OH concentration of 9.651 ppm and 15.573 ppm and P-H3PO4 concentration of 2.013 ppm and 2.7373 ppm. It was marked with additional weight and colour of water hyacinth leaves of fresh green. Mathematical model presented to estimate N concentration decrease rate indicated good result in experiment. However, P concentration decrease in liquid phase, the presented model is still not good, because P nutrient decomposition process has not been accommodated during absorption by water hyacinth.